2013
DOI: 10.1021/jm400722d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Photodynamic Activity of Oligomeric Ethylene Glycol–Quinoline Substituted Zinc(II) Phthalocyanine Derivatives

Abstract: A new series of zinc(II) phthalocyanine derivatives have been synthesized and characterized. These macrocycles exhibited a sharp absorption band in the red visible region in DMF, which indicated that they were dissolved well and almost did not aggregate in this solvent. Compared with the unsubstituted zinc(II) phthalocyanine, all these phthalocyanines have a red-shifted Q-band (at 678-699 vs 670 nm) and exhibit a relatively weaker fluorescence emission and a higher efficiency at generating singlet oxygen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 31 publications
0
35
1
Order By: Relevance
“…It suggested that the AlPc mainly exist as dimer in water. 23,24 Remarkable changes in the Q band region were observed in the presence of BSA ( Fig. 2(a)) and HSA ( Fig.…”
Section: Aggregation Studiesmentioning
confidence: 93%
“…It suggested that the AlPc mainly exist as dimer in water. 23,24 Remarkable changes in the Q band region were observed in the presence of BSA ( Fig. 2(a)) and HSA ( Fig.…”
Section: Aggregation Studiesmentioning
confidence: 93%
“…For these conjugates, zinc(II) phthalocyanine was used as the photosensitizing unit owing to its strong near-infrared absorption efficiency, high efficiency in generating singlet oxygen, and excellent photostability. [45,46] 7-Hydroxycoumarin or 7-hydroxy-4-trifluoromethylcoumarin were selected as the chemotherapeutic cytostatic portions. The two components were linked by a tri(ethylene glycol) chain, which enhances the amphiphilicity and biocompatibility of the system.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…[29] Over the past few years, we have been interested in developing efficient photosensitizers for PDT, especially zinc(II) phthalocyanine derivatives. [30,31] We recently reported two erlotinibzinc(II) phthalocyanine conjugates; erlotinib was chosen as the targeting moiety to conjugate with a zinc(II) phthalocyanine core at the a-position via an oligoethylene glycol spacer, which can improve the amphiphilicity and biocompatibility of the conjugate. By introduction of the erlotinib moiety, the two conjugates exhibited high specificity toward HepG2 cancer cells and A431 tumor tissues in nude mice.…”
Section: Introductionmentioning
confidence: 99%